2014
DOI: 10.1098/rsbl.2014.0175
|View full text |Cite
|
Sign up to set email alerts
|

Mysterious bio-duck sound attributed to the Antarctic minke whale (Balaenoptera bonaerensis)

Abstract: For decades, the bio-duck sound has been recorded in the Southern Ocean, but the animal producing it has remained a mystery. Heard mainly during austral winter in the Southern Ocean, this ubiquitous sound has been recorded in Antarctic waters and contemporaneously off the Australian west coast. Here, we present conclusive evidence that the bio-duck sound is produced by Antarctic minke whales (Balaenoptera bonaerensis). We analysed data from multi-sensor acoustic recording tags that included intense bio-duck so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(98 citation statements)
references
References 9 publications
(13 reference statements)
8
86
3
Order By: Relevance
“…Vocalizations believed to be the ''bioduck'' sound of Antarctic minke whales (Risch et al, 2014) were detected during July and August. Fig.…”
Section: Antarctic Minke Whalesmentioning
confidence: 99%
“…Vocalizations believed to be the ''bioduck'' sound of Antarctic minke whales (Risch et al, 2014) were detected during July and August. Fig.…”
Section: Antarctic Minke Whalesmentioning
confidence: 99%
“…Antarctic mine whales also emit bouts of rapid broadband pulses (which are brief FM downsweeps), sounding like a duck's quack (named the "bioduck" sound). This unique "bioduck" sound has been recorded in Antarctica and off Australia for decades, yet it was not until Risch et al [49], that this sound was positively attributed to Antarctic minke whales. The "bioduck" sound contains pulses of 0.1-0.4-s duration, in bouts of 5-12 pulses, with a 1-3-s interval between bouts, and source levels of 140.2 ± 3.6 dB re 1 µPa rms @ 1 m [49,51].…”
Section: Balaenoptera Acutorostrata-common Minke Whalementioning
confidence: 99%
“…Although some individuals might remain in Antarctica over the winter [47]. In Antarctica, FM downsweeps with a fundamental of 60-140 Hz, occurring with and without harmonics, with a duration of 0.2 ± 0.1 s and a source level of 147.3 ± 5.3 dB re 1 µPa rms @ 1 m have been recorded [48][49][50][51]. Antarctic mine whales also emit bouts of rapid broadband pulses (which are brief FM downsweeps), sounding like a duck's quack (named the "bioduck" sound).…”
Section: Balaenoptera Acutorostrata-common Minke Whalementioning
confidence: 99%
“…Across other oceans, minke whales are known to produce a range of sounds including pulses, clicks, downsweeps, and a variety of other frequency-modulated sounds (e.g., boing, "star wars," and "bio-duck" signals) (e.g., Beamish and Mitchell, 1973;Edds-Walton, 2000;Mellinger et al, 2000;Gedamke et al, 2001;Rankin and Barlow, 2005;Oswald et al, 2011;Risch et al, 2013;Risch et al, 2014). It has been suggested that pulses, the star-wars signals, and boings may act as song.…”
Section: B Dgd and Dgc Are Suspected Whale Callsmentioning
confidence: 99%